Menyoroti Kesenjangan Sosial dalam Tradisi Pemakaman di Desa Sari Rejo - Amelia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Religiousness in the context of religious life in Indonesia is not only seen in the diversity between religions, but also within the same religion with differences in religious beliefs and practices. Each individual or group has its own way of expressing their beliefs, which are often influenced by local cultural backgrounds and traditions. Indonesia, as a country rich in culture, has a legacy of traditions that are still embedded in people's lives, including in religious practices. In Sari Rejo Village, the funeral procession is one concrete manifestation of the fusion of religious values ​​and hereditary traditions. However, within the community there are groups who adhere to pure Islamic law, without mixing religious teachings with ancestral traditions. This difference in perspective triggers social conflict between adherents of religious law and adherents of tradition. This conflict does not stop at differences in practice, but develops into a form of social discrimination against adherents of religious law. This condition gives rise to social inequality that can disrupt the harmony of community life. This study aims to answer several main questions: (1) what is the form and meaning of funeral traditions in Sari Rejo Village? (2) why social inequality arises in these funeral ceremonies? (3) how are traditional adherents treated differently compared to those who adhere to religious law? (The text appears to be incomplete and should be omitted.) The research method used is a qualitative method, relying on primary data, secondary data, and direct field observations. The results show that the majority of Sari Rejo residents, as adherents of tradition, tend to discriminate against those who adhere to religious law. This is evident in the differences in treatment, attitudes, and social acceptance of those who choose to practice their religion according to its guidance without incorporating traditional elements. These findings emphasize that differences in religious practices, even within the same religion, can become a source of social inequality if not managed wisely.